The Development of Piano and Its Impact on Composers - Shi, Minqi (Journal of Theory and Practice of Social Science, 2024)
Keyboard instruments have evolved over the centuries. Their development and composers are deeply intertwined as the evolution significantly influenced how composers composed music and the genres created. Keyboard instruments were not widely used before the Renaissance and Baroque periods, as the majority was vocal music. The renowned composer J. S Bach changed the way keyboard instruments were traditionally used after the development of the harpsichord. The Brandenburg Concerto No. 5 in D major, BWV 1050, in particular, is notable for its solo part in the setting of a chamber work. The "Well-Tempered Clavier", intrinsically tied to the invention of the clavier, paved the way for solo keyboard works. Around 1700, the fortepiano invented by Bartolomeo Cristofori offered composers, like Mozart and Beethoven, a new range of dynamics and expressive possibilities. During the Romantic era, improvements were made to the piano's mechanism for the purpose of expanding the instrument's abilities. This allowed composers to create more complex compositions in a greater and more expressive range. Leading up to the 20th century, pianos were no longer treated as melodic instruments, instead becoming a percussive instrument that composers experimented with in various ways. In this essay, I will discuss the history of the piano, its development and the impact it had on composers.